Profiling stroking parameters management in front crawl - Seifert, L.; Guignard, B.; Regaieg, M. A.; Létocart, A.; Carmigniani, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
In cyclic activities such as swimming, speed (S, in m/s) is the product of stroke length (SL, in m/cycle) and stroke rate (SR, in cycle/min). However, to swim faster an athlete can adopt different strategies of SR-SL combination. Hay (2002), and Seifert and Chollet (2009) have modelled the relationships between SR and S and between SL and S by quadratic regression. Recent findings have shown that the increase of S in front crawl can be achieved through two regimes of functioning (Carmigniani et al., 2020): (i) First, at low pace and low drag, swimmers minimise energy consumption, exhibiting a stable SL, a catch-up pattern of coordination (i.e., a lag time between two propulsive actions of the upper limbs measured by the index of coordination; Chollet et al., 2000), and increase S mainly by increasing SR. In fact, at low pace, an optimal coordination (i.e., catch-up pattern) exists independently of the speed. The swimmers kept a constant index of coordination and varied their speed by increasing their mean propulsive force. This seems similar to the burst-and-coast swimming behaviour observed for certain fish such as cod or saithe. A model to explain this behaviour was proposed by (Videler & Weihs, 1982). They found that if the fish had a reduced drag during the gliding phase they could consume less mechanical energy to maintain the same average velocity than in steady swimming. The extended arm during the gliding phases in front-crawl can be interpreted as a way to reduce the body drag. (ii) Second, when S and drag increase, and when they reached their upper bound of force, the propulsion time was minimal and did not vary. To further increase their speed, they had to reduce their non-propulsive phases (recovery, entry and catch) and the time between two propulsive phases. Thus, the swimmers used a maximal force regime characterised by high increase of SR and of the continuity between propulsive actions, which above 1.8 m/s led to a superposition pattern of coordination (Carmigniani et al., 2020; Seifert & Carmigniani, 2021). Thanks to the burst-and-coast approach, Carmigniani et al. (2020) provide insights into the nonlinear change in the motor organisation (e.g. arm coordination) with swimming speed and the leading parameters (SR and SL) that influence the optimal choice of motor coordination. The first aim of our study was to compute a simplified modelling of the two regimes of functioning based only on S-SR relationships. Then, beyond this general law, one can wonder how swimmers individually select a strategy of SR-SL combination; therefore, our second aim was to investigate different profiles of S-SR relationships management.